2021
DOI: 10.1111/jcpt.13569
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of ciclosporin in allogeneic hematopoietic stem cell transplant recipients: C‐reactive protein as a novel covariate for clearance

Abstract: What is known and objectives Ciclosporin (CsA), a potent immunosuppressive agent used to prevent graft‐versus‐host disease in allogeneic hematopoietic stem cell transplant (allo‐HSCT) recipients, is characterized by large inter‐individual variability and a narrow therapeutic range. The aim of this study was to develop a population pharmacokinetic model for CsA in Chinese allo‐HSCT recipients and to identify covariates influencing CsA pharmacokinetics. Methods A total of 758 retrospective drug monitoring data p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…For example, a more individualized pharmacokinetic dosing of vancomycin in a critically ill patient contributed to a faster achievement of the target value without increased nephrotoxicity [ 30 ]. Recently, the patient C-reactive protein (CRP) was identified as a significant covariate affecting the pharmacokinetics of CsA, indicating that a higher daily dose is required to achieve therapeutic trough concentrations at high CRP levels [ 31 ]. Since each patient has unique characteristics, immunosuppression has to be questioned to follow a uniform regimen [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a more individualized pharmacokinetic dosing of vancomycin in a critically ill patient contributed to a faster achievement of the target value without increased nephrotoxicity [ 30 ]. Recently, the patient C-reactive protein (CRP) was identified as a significant covariate affecting the pharmacokinetics of CsA, indicating that a higher daily dose is required to achieve therapeutic trough concentrations at high CRP levels [ 31 ]. Since each patient has unique characteristics, immunosuppression has to be questioned to follow a uniform regimen [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant drugs, such as anabolic steroids ( Ni et al, 2013 ) and triazole antifungal agents ( Zhou et al, 2012 ; Li et al, 2019 ; Ling et al, 2021 ), have been reported to affect CsA PK exposure. Children undergoing IST often receive steroids as a concomitant drug ( Ettenger, 1998 ; Benfield et al, 1999 ; Clucas et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 9 , 16 CsA has high interindividual variability, 17 and its pharmacokinetics are affected by numerous factors, including demographic characteristics, hematocrit, liver function, and triazole antifungal agents. 18 21 In a previous study, a population pharmacokinetic (PopPK) model for CsA was established in Chinese HSCT patients, 18 and the exposure (area under the concentration–time curve, AUC) of CsA could be estimated by this model. Some previous studies have explored the relationship between the concentration of CsA and the occurrence of aGVHD.…”
Section: Introductionmentioning
confidence: 99%